The implantation process of oral health services in indian communities of the rivers Tiquié and Uaupés – special indian sanitary district for the Alto Rio Negro – Amazonas - Nunes, Selma Aparecida Chaves; Lauris, José Roberto Pereira; Tomita, Nilce Emy (Tempus – Actas de Saúde Coletiva, 2013)
This study reconstitutes the implantation process of oral health services in Indian communities of the rivers Tiquié and Uaupés – Special Indian Sanitary District for the Alto Rio Negro – Amazons. In the political, administrative, anthropological and socioeconomic context, it aims at identifying its contribution to the organization of basic attention in oral health and its reflexes in the assistance provided. The reality in the realm of contracts 439/99 and 2349/00 is established as a recut, celebrated between Fundação Nacional de Saúde and the Associação Saúde Sem Limites in the period of 2000 – 2001 which object is the organization of health services in the Tiquié and Uaupés rivers area, in the implantation process context at the Rio Negro’s Special Indian Sanitary District. It reveals the strategical dimension of establishing, in the field of organization and operation of the services, the guiding principles of Unique Health System. It points out, as fundamental in the oral health basic attention, the local planning, with emphasis in a greater visualization of life reality of the local population. Its daily practice reflects the restrictions regarding the political, technical and administrative sectors in order to define projects propose intervention mechanisms, allocate and manage the existing resources and the potential ones including human resources. It is necessary that the managers assume the challenges of power, work and knowledge relations between the population and the professionals and among different groups of these segments.